Music Therapy and Emotional Well-being: A Narrative Review of Global Practices and Outcomes - Nuristama, Ramadhina Ulfa (Indonesian Scientific Publication, 2024)
Music therapy has gained increasing attention as an effective intervention for improving emotional well-being in diverse populations. This narrative review aimed to synthesize recent literature across clinical, educational, community, and cross-cultural contexts to assess the effectiveness and limitations of music-based interventions. A systematic search of databases including PubMed, Scopus, Web of Science, and Google Scholar was conducted using targeted keywords and Boolean combinations. Eligible studies encompassed randomized controlled trials, observational research, and qualitative analyses that explicitly examined the relationship between music therapy and psychological outcomes. The results indicate that music therapy consistently reduces symptoms of depression, anxiety, and PTSD, while enhancing cognitive and emotional functioning in stroke rehabilitation and improving quality of life in palliative care. In schools, music therapy programs were found to promote emotional regulation, empathy, and social connectedness, with culturally responsive interventions showing greater effectiveness for diverse student populations. Community and correctional settings further demonstrated music therapy’s capacity to foster social reintegration, reduce stigma, and strengthen coping mechanisms. Comparative evidence suggests that music therapy offers distinct benefits compared with other psychosocial interventions, particularly due to its ability to evoke immediate emotional and cognitive responses. However, methodological inconsistencies, limited cross-cultural studies, and systemic barriers such as inadequate funding and workforce shortages remain key challenges. The review underscores the urgency of integrating music therapy into public health and education policies, while calling for future research that employs standardized, longitudinal, and culturally inclusive approaches. By leveraging community engagement and technological innovation, music therapy can be positioned as a vital, evidence-based strategy for advancing global emotional well-being.